Mengakar Pancasila dalam Diri Mahasiswa: Aktualisasi Pancasila dalam Kehidupan Kampus Melalui Implementasi Tridharma Perguruan Tinggi - Rahma, Resa Kurnia (Maliki Interdisciplinary Journal, 2025)
This article discusses the application of Pancasila in the Tri Dharma of Higher Education: education, research, and community service. In education, Pancasila is integrated into the curriculum and student activities to shape character based on the values of unity, tolerance, and cooperation. In research, Pancasila serves as an ethical foundation for scientific works that benefit society, while in community service, Pancasila values are applied through community empowerment and welfare improvement. Challenges such as globalization and the commercialization of education need to be addressed by strengthening character education and digital literacy to optimize the application of Pancasila in higher education. Other challenges include a lack of in-depth understanding of Pancasila and partial implementation. So that this challenge can be overcome, comprehensive steps are needed, such as strengthening character education and digital literacy